Contextual Teaching and Learning with Instructional Video Support: Its Impact on Mathematics Achievement across Levels of Prior Knowledge - Nuraeni, Nuraeni; Baharullah, Baharullah; Saleh, Sitti Fitriani; Moguel, Landy Sosa (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
Mathematics learning in secondary schools often encounters obstacles due to the abstract nature of the subject matter and students’ negative perceptions of mathematics as a difficult discipline. This condition demands instructional innovations that not only link concepts to real-life contexts but also employ digital media to strengthen understanding. This study aimed to analyze the effect of Contextual Teaching and Learning (CTL) assisted by video on junior high school students’ mathematics achievement, with prior ability considered as a moderating variable. A quasi-experimental method with a 2×2 factorial design was employed. The research population comprised all Grade VII students of SMP Semen Tonasa (N = 179), with two classes selected through cluster random sampling. The instruments included a prior ability test, a multiple-choice mathematics achievement test, and an observation sheet of instructional implementation. All instruments were validated through expert judgment and empirical testing, yielding a reliability coefficient of 0.87, item difficulty indices in the moderate range (0.31–0.70), and most discrimination indices in the good category. The research procedure consisted of preparation (module development, instrument validation, and class assignment), implementation (pretest, CTL with/without video, posttest), and reporting. Data were analyzed using Two-Way ANOVA after meeting the assumptions of normality (Kolmogorov–Smirnov, p > 0.05) and homogeneity (Levene’s Test, p > 0.05).